2016
DOI: 10.1007/s11104-016-2818-0
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhizal community structure on co-existing tropical legume trees in French Guiana

Abstract: Aims: We aimed to characterise the arbuscular mycorrhizal fungal (AMF) community structure and potential edaphic determinants in the dominating, but poorly described, root-colonizing Paris-type AMF community on co-occurring Amazonian leguminous trees. Methods:We targeted three highly productive leguminous trees Results: Classical approaches targeting abundant SSU ampliconshighlighted a diverse root-colonizing symbiotic AMF community dominated by members of the Glomeraceae. DGGE profiling indicated that, of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 65 publications
2
10
0
Order By: Relevance
“…SMITH & SMITH (2011a) reported that intracellular hyphae, arbuscules, and structures with intermediate morphology are involved in the transfer of nutrients to the host plant, not arbuscules alone. Therefore, the presence of the Paris morphological pattern in acerola roots is a positive factor for nutrient absorption in the crop, enhancing plant growth, which was also noted in other plant species in a study conducted by BREARLEY et al (2016). Similar findings were also reported by HARIKUMAR et al (2015) in plants with the Paris morphological pattern with satisfactory growth.…”
Section: Resultssupporting
confidence: 84%
“…SMITH & SMITH (2011a) reported that intracellular hyphae, arbuscules, and structures with intermediate morphology are involved in the transfer of nutrients to the host plant, not arbuscules alone. Therefore, the presence of the Paris morphological pattern in acerola roots is a positive factor for nutrient absorption in the crop, enhancing plant growth, which was also noted in other plant species in a study conducted by BREARLEY et al (2016). Similar findings were also reported by HARIKUMAR et al (2015) in plants with the Paris morphological pattern with satisfactory growth.…”
Section: Resultssupporting
confidence: 84%
“…Most VT detected in this study belonged to the Glomeraceae, which is the most widespread family in natural and managed ecosystems (Lumini et al ., ; Oehl et al ., ; Brearley et al ., ). Surprisingly, Paraglomeraceae, a family rarely detected in high numbers even in other tropical and temperate grasslands (Uhlmann et al ., ; Moora et al ., ; Xiang et al ., ) was the most abundant family in Gorongosa National Park (GNP) grasslands.…”
Section: Discussionmentioning
confidence: 98%
“…Other studies using ribosomal DNA barcodes (not necessarily the ITS1 barcoding region) to distinguish taxa have encountered high AMF diversity in tropical forests: Husband et al (2002) found 30 OTUs associating with two tree species, and Haug et al (2010) found 102 AMF associating with 23 different tree genera. Another study detected 34 taxa associating with two tree species using denaturing gradient gel electrophoresis (Brearley et al 2016). To our knowledge, no other study has identified a greater alpha diversity of AMF at one site (but see discussion on limitations of DNA metabarcoding below).…”
Section: Discussionmentioning
confidence: 96%
“…Another study detected 34 taxa associating with two tree species using denaturing gradient gel electrophoresis (Brearley et al . ). To our knowledge, no other study has identified a greater alpha diversity of AMF at one site (but see discussion on limitations of DNA metabarcoding below).…”
Section: Discussionmentioning
confidence: 97%